2014
DOI: 10.1249/mss.0000000000000306
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Muscle Power and the Slow Component of O2 Uptake

Abstract: The findings of this investigation support the thesis that the energetic contribution from respiratory muscles to the V˙O2sc amplitude is disproportionately higher during severe- compared with that during heavy-intensity exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…Recently, Oueslati et al [15] showed a significant correlation between the VO 2 SC and the decline in maximal inspiratory and expiratory pressure during a constant-load exercise at 85% of maximal aerobic power. These results corroborate those of Cross et al [16,17] showing that the VO 2 SC is strongly related to respiratory muscle work during a constant-load exercise at a work rate roughly equal to 25% and 60% of the difference between the GET and VO 2peak . Potential limitations of the aforementioned studies include unique exercise intensity being studied and the fact that exercise was not conduct until exhaustion.…”
Section: Despite Decades Of Research the Vo 2 Sc Underpinning Mechansupporting
confidence: 92%
“…Recently, Oueslati et al [15] showed a significant correlation between the VO 2 SC and the decline in maximal inspiratory and expiratory pressure during a constant-load exercise at 85% of maximal aerobic power. These results corroborate those of Cross et al [16,17] showing that the VO 2 SC is strongly related to respiratory muscle work during a constant-load exercise at a work rate roughly equal to 25% and 60% of the difference between the GET and VO 2peak . Potential limitations of the aforementioned studies include unique exercise intensity being studied and the fact that exercise was not conduct until exhaustion.…”
Section: Despite Decades Of Research the Vo 2 Sc Underpinning Mechansupporting
confidence: 92%
“…; Cross et al. , ) and have demonstrated clinical usefulness by helping guide mechanical ventilation therapy (Talmor et al. ; Plataki and Hubmayr ; Akoumianaki et al.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters include the resistance and compliance of the lungs and chest wall, intrinsic positive end-expiratory pressures, and respiratory muscle work and fatigue. These parameters offer insight into the energetics of respiratory muscle work in healthy and clinical populations (Johnson et al 1992(Johnson et al , 1993(Johnson et al , 1996Prigent et al 2008;Cross et al 2012Cross et al , 2014 and have demonstrated clinical usefulness by helping guide mechanical ventilation therapy (Talmor et al 2008;Plataki and Hubmayr 2011;Akoumianaki et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The raw, uncorrected MEFV curve was obtained from the single effort with the largest VC, and most positive peak expiratory P OES , from the GVC maneuvers performed at ~100% of maximum effort; this raw curve is referred to hereafter as MEFV raw . The TGC-corrected MEFV envelope was obtained by taking the highest FEF observed at a given lung volume across all GVC efforts (Cross et al, 2018;Cross, Winters, Sheel, & Sabapathy, 2014;Guenette et al, 2010;Olafsson & Hyatt, 1969). This "maximal perimeter" MEFV curve is thought to mitigate the issue(s) associated with TGC during forced expirations (Cross et al, 2014(Cross et al, , 2018Guenette et al, 2010;Olafsson & Hyatt, 1969).…”
Section: Graded Vital Capacity Maneuversmentioning
confidence: 99%